Kaip šiandien lietuviškoje istoriografijoje keičiasi žvilgsnis į Lietuvos Didžiosios Kunigaikštijos epochą? - Jarutis, Vytautas (Lietuvos istorijos studijos, 2011)
The aim of the article is to evaluate the methodological and ideological developments in the historiography of the epoch of the Grand Duchy of Lithuania in the comparative perspective of the last century. Methodologically, "the Golden Age" is exactly recorded at present in the Lithuanian historiography of the Grand Duchy of Lithuania. After reestablishing independence in 1990, Lithuanian historians refused the heritage of Soviet historiography, started integrating the Western theoretical discourse and have created a unique model of the development of the Grand Duchy of Lithuania in the European civilization, proposed by Edvardas Gudavičius. The receptions and transformations of this paradigmic model have been continuing until now in the transition from the political history to the history of society and everyday life, from an ethnolinguistically monoperspective to the liberal multicultural great narrative. Ideologically, the developments in the Lithuanian historiography of the Grand Duchy of Lithuania are analyzed on the basis of nowadays' comparative studies of nationalism. This allowed to uncover the ethnocultural positions of interwar Lithuanian historians, the intuitionalism of the Soviet times and the constructivism of today, which implicate the cognitive step from "the plough of the nation" to the "Lithuanian europeism" in the Lithuanian collective consciousness.